2021
DOI: 10.21608/adjg.2021.43369.1296
|View full text |Cite
|
Sign up to set email alerts
|

The Synergetic Effect of Silver Diamine Fluoride with Potassium Iodide and Grape Seed Extract on Dentin Remineralization

Abstract: Purpose: This study was conducted to evaluate the synergetic effect of using silver diamine fluoride containing potassium iodide and grape seed extract on dentin microhardness. Materials and Methods: Sixty freshly extracted human deciduous second molars were enrolled in this study. Sixty dentin discs were cut from the crown and were randomly divided into four groups according to the applied treatment after dentin demineralization, (15 samples each). In the first group, samples were received no treatment, only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…This stabilized collagen matrix could serve as a mechanical Evaluation of Remineralizing Potential of Cranberry and Chitosan on Demineralized Dentin (91) barrier, which inhibits the adverse effect of acid and further loss of minerals (19) . These findings are in accordance with previous studies (3,12) which evaluated the remineralizing effect of proanthocyanidin on demineralized dentin and recorded significant increase in dentin microhardness after treatment with proanthocyanidin. However, the current findings are in contrary with previous studies (24,25) which revealed that demineralized dentin treated with proanthocyanidin did not show any significant increase in dentin microhardness.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…This stabilized collagen matrix could serve as a mechanical Evaluation of Remineralizing Potential of Cranberry and Chitosan on Demineralized Dentin (91) barrier, which inhibits the adverse effect of acid and further loss of minerals (19) . These findings are in accordance with previous studies (3,12) which evaluated the remineralizing effect of proanthocyanidin on demineralized dentin and recorded significant increase in dentin microhardness after treatment with proanthocyanidin. However, the current findings are in contrary with previous studies (24,25) which revealed that demineralized dentin treated with proanthocyanidin did not show any significant increase in dentin microhardness.…”
Section: Discussionsupporting
confidence: 93%
“…ANOVA repeated measures was performed to compare the effect of evaluation time on microhardness and percentage of change of microhardness within each treatment group. Percentage of change (MH%) of dentin was calculated according to a previous study (3)…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations